2020
DOI: 10.2196/20623
|View full text |Cite
|
Sign up to set email alerts
|

Converting Visitors of Physicians’ Personal Websites to Customers in Online Health Communities: Longitudinal Study

Abstract: Background With the dramatic development of Web 2.0, increasing numbers of patients and physicians are actively involved in online health communities. Despite extensive research on online health communities, the conversion rate from visitor to customer and its driving factors have not been discussed. Objective The aim of this study was to analyze the conversion rate of online health communities and to explore the effects of multisource online health com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Patients can gain insight into a physician's past efforts through web-based behaviors, which may influence their attitudes toward the physician, thereby influencing the likelihood of selecting that physician [6]. Most importantly, physicians' web-based behaviors are important cues for evaluating service process quality [14,16]. Combined with health care service characteristics [2][3][4], patients prefer to choose physicians who can provide a high-quality service process.…”
Section: Log-in Behavior and Web Reviewsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients can gain insight into a physician's past efforts through web-based behaviors, which may influence their attitudes toward the physician, thereby influencing the likelihood of selecting that physician [6]. Most importantly, physicians' web-based behaviors are important cues for evaluating service process quality [14,16]. Combined with health care service characteristics [2][3][4], patients prefer to choose physicians who can provide a high-quality service process.…”
Section: Log-in Behavior and Web Reviewsmentioning
confidence: 99%
“…In OHCs, web reviews are generated by patients who have experienced health care services. The more web reviews about a physician presented in the OHC, the more patients have selected the physician for consultation [16]. The web reviews generated by patients with similar experiences are more objective and credible signals than traditional information from acquaintances [40], which can increase other patients' trust in the physician and reduce perceived risks [41].…”
Section: Hypothesis 1: a Physician's Log-in Behavior Has A Positive Effect On Patient Consultationmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients and physicians display different signals on e-consultation websites, affecting patients’ cognitive abilities to choose a good doctor [ 16 ]. People obtain information regarding the quality of healthcare services rendered by physicians through different signaling mechanism [ 25 ], such as the process that the signaler (i.e., the physician) sends measurable signals (i.e., offline reputation as physician title, education, experience and online effort) to the recipient (i.e., patients) to communicate details about the non-observable qualities (i.e., competency) in order to minimize information asymmetry [ 21 , 26 ]. Earlier research indicated that receivers are sovereign decision-makers [ 27 ].…”
Section: Introductionmentioning
confidence: 99%